2013
DOI: 10.1111/1346-8138.12296
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte and monocyte adsorption apheresis for Behçet's disease in a pregnant woman

Abstract: We present a 39-year-old pregnant woman with Behçet's disease who was treated successfully with granulocyte and monocyte adsorption apheresis (GMA). There were no complications or adverse effects during her pregnancy and delivery. The neonate manifested no abnormalities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…GCAP was initially approved for the treatment of UC . Later, it was shown to be effective on various skin conditions, such as generalised pustular psoriasis, psoriatic arthritis, systemic lupus erythematosus skin rash, Behcet's disease and PG .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GCAP was initially approved for the treatment of UC . Later, it was shown to be effective on various skin conditions, such as generalised pustular psoriasis, psoriatic arthritis, systemic lupus erythematosus skin rash, Behcet's disease and PG .…”
Section: Discussionmentioning
confidence: 99%
“…GCAP was initially approved for the treatment of UC (5-7). Later, it was shown to be effective on various skin conditions, such as generalised pustular psoriasis, psoriatic arthritis, systemic lupus erythematosus skin rash, Behcet's disease and PG (8)(9)(10)(11)(12)(13)(14)(15)(16)(17). The efficacy of GCAP has been reported in some patients with both PG and an inflammatory bowel disease (either UC or CD) (13,18,19), but only seven patients with PG have been successfully treated with this apheretic technique (14)(15)(16)(17).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In pregnant women, these systemic agents raise fetal risks such as teratogenicity, stillbirth and spontaneous abortion ( 68 ). GMA could be a valid treatment option in BD, since neutrophils are involved in its etiopathogenesis, as shown in Table IV ( 28 , 71 , 72 ). In their case series, Sakanoue et al ( 28 ) performed GMA five times, once a week, for the majority of patients.…”
Section: Application Of Gma In Neutrophilic Dermatosesmentioning
confidence: 99%
“…Very little is known about the influence of BD and pregnancy to date. In few anecdotal case reports and retrospective small sample studies, both remissions and flares during pregnancy have been reported, and the effect of the disease on pregnancy remained unclear [1][2][3][4][13][14][15][16][17][18][19][20][21][22]. Based on previous studies, it can be concluded that disease activity usually regresses during pregnancy.…”
Section: Introductionmentioning
confidence: 99%